INTRODUCING A REVOLUTIONARY INVERTER UTILIZING SNUBBERLESS DC-DC CONVERTERS (International Journal of Food and Nutritional Sciences, 2022)
The inverter under consideration is a dc/dc converter without a snubber. The majority of dc-dc converters require snubber circuits to reduce voltage surges. When a traditional dc-dc converter is shut off, voltage overshoot occurs in all semiconductor components. An additional snubber circuit or voltage clamping is necessary to reduce voltage overshoot. The efficiency of the converter diminishes as the losses and number of components grow. This problem is overcome by using secondary modulation to run the converter with soft-switching capabilities. As a result, no additional snubber is required. This architecture employs Zero Voltage Switching (ZVS) and Zero Current Switching (ZCS). The converter controls activate at ZVS and deactivate at ZCS. It is recommended to use a voltage converter with a high step-up voltage conversion ratio. The dc-dc converter's output is then connected to a thorough bridge inverter. The inverter's output alternating current is connected to the grid or supply. These inverters with snubberless dc/dc converters are typically employed in fuel cell automobiles, energy storage systems, and home photovoltaic (PV) applications. Simulink Model (Matlab Software) tools were used to model the designed system